DIGITAL MARKETING AND SMES'S PERFORMANCE IN WEST SUMATERA (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2020)
This study investigated the effects of digital marketing use on Small Medium Enterprises’ (SMEs) performance. The objectives are to asseses the effect of effort expectancy, social influence, and facilitating condition on digital marketing use and business performance of SMEs in West Sumatra. The research population is focused on SMEs on culinary sector in West Sumatra who have used digital marketing. A total of 162 respondents were taken based on urban areas in West Sumatera, Padang, Bukittinggi, Padang Panjang, Solok and Payakumbuh. The primary data include a structured questionnaire used to elicit information from the target respondents. The Structural Equation Model (SEM) used to test the hypotheses that were generated for the study. The findings showed that effort expectancy, social influence, and facilitating condition has a significant effect on digital marketing use and business performance of SME’s in West Sumatra.